Ozonolysis of α-amino-α/-hydroxymethyl-4-nitroacetophenone in the liquid phase - G. A. Galstyan (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2017)
Recent studies have shown that the existing problems on levomycetin synthesis can be solved involving ozone as technologicaly undiluted oxidant.